2023
DOI: 10.1111/jgh.16424
|View full text |Cite
|
Sign up to set email alerts
|

FODMAP meal challenge test: a novel investigation to predict response to low‐FODMAP diet in non‐constipating irritable bowel syndrome

Uday C. Ghoshal,
Uzma Mustafa,
Subhra K. Mukhopadhyay

Abstract: BackgroundThough a low‐FODMAP diet improves 50% irritable bowel syndrome (IBS) patients, regional dietary variations, vegetarianism, and long‐term nutritional consequences challenge its implementation. We aimed developing a FODMAP meal challenge test (FMCT). We prospectively studied whether (i) high‐ than low‐FODMAP foods produce more breath H2 among IBS patients than controls; (ii) post‐meal symptoms relate to breath H2; and (iii) novel FMCT predicts response to a low‐FODMAP diet?MethodsForty Rome III IBS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In a recent limited pilot investigation, the positive FODMAP meal challenge test (indicated by breath H2 levels exceeding 10 PPM above baseline accompanied by symptoms after consuming a high FODMAP meal) demonstrated sensitivity, specificity, and diagnostic accuracy of 78.6%, 66.6%, and 75.6%, respectively, in forecasting the response to a low FODMAP diet [121].…”
Section: Breath Testmentioning
confidence: 99%
“…In a recent limited pilot investigation, the positive FODMAP meal challenge test (indicated by breath H2 levels exceeding 10 PPM above baseline accompanied by symptoms after consuming a high FODMAP meal) demonstrated sensitivity, specificity, and diagnostic accuracy of 78.6%, 66.6%, and 75.6%, respectively, in forecasting the response to a low FODMAP diet [121].…”
Section: Breath Testmentioning
confidence: 99%
“…The sensitivity observed by Somvanapanich et al 1 (66.7%) is lower than our study (78%). 4 The above-mentioned factors might explain the difference in sensitivity in these 2 studies. 1 , 4 We believe that studying breath H 2 over a longer duration along with symptoms generation is expected to predict microbial metabolic index in the gut lumen and visceral hypersensitivity to predict response to a low-FODMAP meal as reported by us recently.…”
mentioning
confidence: 92%
“… 3 In our recent study on FODMAP-meal challenge test, we observed that rise in breath H 2 was most prominent after the first 4 hours of ingestion of a standardized high FODMAP meal. 4 Somvanapanich et al 1 claimed that they replicated their previous protocol wherein, rise in breath H 2 was not observed after breakfast until 2 hours post-lunch. 5 However, it raises a question whether 2-hour post-lunch rise is exclusively attributed to lunch and not influenced by the breakfast.…”
mentioning
confidence: 94%